SUSTAINABILITY AND ENVIRONMENTAL ISSUES IN INTERNATIONAL BUSINESS: GREEN ECONOMY AND ESG PRINCIPLES - Dilshod Yuldoshevich Goyibov (Ecomind Press, 2025)
Sustainability and environmental issues have become integral aspects of international business operations, influencing corporate strategies and global economic trends. The shift towards a green economy and the implementation of ESG (Environmental, Social, and Governance) principles have gained significant attention in recent years. Companies are increasingly required to integrate sustainable practices into their operations, addressing concerns such as carbon emissions, resource efficiency, and ethical business conduct. This paper explores the role of sustainability in international business, the challenges faced by organizations in adopting green economy principles, and the impact of ESG criteria on investment and corporate decision-making. The research highlights how multinational corporations and emerging markets, including Uzbekistan, are adapting to these global changes. The study also examines the influence of regulatory frameworks, consumer preferences, and technological advancements on sustainable business models. By analyzing key trends and case studies, this paper provides insights into the opportunities and challenges associated with sustainability in international business, emphasizing the need for companies to align their strategies with environmental and social responsibilities.
Keywords: Sustainability, Environmental issues, International business, Green economy, ESG principles, Corporate responsibility, Sustainable development, Investment trends, Business ethics, Climate change adaptation.